Influence of dentin pretreatment on bond strength of universal adhesives - Claudio Poggio; Riccardo Beltrami; Marco Colombo; Marco Chiesa; Andrea Scribante (Taylor & Francis Group, 2017)
Objective: The purpose of the present study was to compare bond strength of different universal adhesives under three different testing conditions: when no pretreatment was applied, after 37% phosphoric acid etching and after glycine application. Materials and methods: One hundred and fifty bovine permanent mandibular incisors were used as a substitute for human teeth. Five different universal adhesives were tested: Futurabond M+, Scotchbond Universal, Clearfil Universal Bond, G-Premio BOND, Peak Universal Bond. The adhesive systems were applied following each manufacturer's instructions. The teeth were randomly assigned to three different dentin surface pretreatments: no pretreatment agent (control), 37% phosphoric acid etching, glycine pretreatment. The specimens were placed in a universal testing machine in order to measure and compare bond strength values. Results: The Kruskal-Wallis analysis of variance and the Mann-Whitney test were applied to assess significant differences among the groups. Dentin pretreatments provided different bond strength values for the adhesives tested, while similar values were registered in groups without dentin pretreatment. Conclusions: In the present report, dentin surface pretreatment did not provide significant differences in shear bond strength values of almost all groups. Acid pretreatment lowered bond strength values of Futurabond and Peak Universal Adhesives, whereas glycine pretreatment increased bond strength values of G Praemio Bond adhesive system.